Some hydrodynamic problems for flood forecasting and flood control in the Red river system - Diep, Nguyen Van (Vietnam Journal of Mechanics, 2007)
My research & development activity in the field of environmental & natural fluid mechanics has been started after one year’s working visit, proposed by Prof. Nguyen Van Dao, at the Laboratoire National d’Hydraulique de France in Chatou, France (1979-1980). Until now this activity is still a most important one. In the paper it is presented some selected scientific results in one of hydrodynamic problems for flood forecasting and flood control: developing of the 1D hydraulic model, 1D & quasi 2D model, 1D hydraulic model for dam break flow , 2D hydraulic model, coupling of 1D and 2D hydraulic models and some theirs applications for flood forecasting and flood control in the Red River System. This paper is dedicated to the memory of Prof. Nguyen Van Dao, with whom I had a big chance to work and to collaborate during about 30 years, to whom I would like to express my heartfelt thanks.